2005
DOI: 10.1590/s0103-90162005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Gafsa rock phosphate and triple superphosphate for dry matter production and P uptake by corn

Abstract: Crops in general make poor use of phosphorous fertilizer and, as a result, recommended rates and production costs are very high. Phosphorus can be made more readily available to plants by proper management of phosphate fertilization, selecting both, type of fertilizer and application method. This study was carried out to evaluate the efficiency of the natural Gafsa rock phosphate and the triple superphosphate on dry matter production and P uptake by corn plants cultivated in a greenhouse. Fertilizers were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
1
11
0
12
Order By: Relevance
“…In little weathered or organic matter -rich soils, with strong preponderance of negative over positive charges, solubilization of RPhs is most likely primarily caused by Ca 2+ consumption released from phosphate by the soil CEC (Corrêa et al, 2005), so that the effect of contact time on plant growth is less negative or even insignificant. Under these conditions, the P plant drain can become more effective than the P soil drain during the contact period, controlling the solubilization kinetics and P availability to plants.…”
Section: Effect Of Contact Timementioning
confidence: 99%
See 1 more Smart Citation
“…In little weathered or organic matter -rich soils, with strong preponderance of negative over positive charges, solubilization of RPhs is most likely primarily caused by Ca 2+ consumption released from phosphate by the soil CEC (Corrêa et al, 2005), so that the effect of contact time on plant growth is less negative or even insignificant. Under these conditions, the P plant drain can become more effective than the P soil drain during the contact period, controlling the solubilization kinetics and P availability to plants.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…A removal or reduction of the levels of these phosphate dissolution products from its proximity increases the solubilization rate of RPhs. In laboratory and greenhouse studies, respectively, Robinson & Syers (1990) and Corrêa et al (2005) showed that the Ca-drain was most important for the solubilization of Gafsa RPh, compared with the P-drain or even with the pH. Some questions may arise regarding the MR and its behavior as multiple extractor, which could simplify the routine of soil analysis laboratories (Raij et al, 1986), based on comparisons of the behavior of this extractor with that of the plant, and the dependence of P extraction from RPhs with Ca 2+ extraction as well.…”
Section: Effect Of P-drain and Ca-drainmentioning
confidence: 99%
“…O milho crescido no LU respondeu à localização do P, com maiores produções em resposta a uma localização maior do elemento (Tabela 3), em concordância com os resultados reportados por Silva et al (2004) e Corrêa et al (2005). Esta resposta verificada no material mais pobre em P e mais argiloso, não foi evidenciada no PVA, de textura média e com maior disponibilidade inicial do nutriente (Tabela 1 e 2), sugerindo que o método de aplicação assumiria menor importância em solos com elevada disponibilidade de P. Os solos semelhantes ao PVA, com menor fator capacidade, possibilitam melhor aproveitamento do P pelas plantas, quando a água não é fator limitante à produção (Costa et al, 2006;Farias et al, 2008).…”
Section: Figuraunclassified
“…De acordo com Corrêa et al (2005), o teor e o tipo de argila, a capacidade de troca de cátions (CTC), o poder tampão, a adsorção de Ca e de P, o teor de matéria orgânica e a umidade, afetam a solubilização de P no solo e, consequentemente, sua extração. Segundo alguns autores (Rolim Neto et al, 2004;Silva et al, 2004;Rocha et al, 2005) o aumento do poder tampão de fosfato do solo diminui a extração de P do solo pelos extratores constatando-se que, em solo com menor teor de argila, elevado valor de P remanescente (P-rem) e baixa CMAP, as extrações de P são maiores.…”
unclassified